Development of a Concrete-Representational-Abstract (CRA) Approach-Based Student Worksheet to Facilitate Students' Mathematical Modeling Skills in Support of SDG 4 - Fitra Maulana Zasqi; Memen Permata Azmi (Suska Journal of mathematics Education, 2026)
A needs analysis revealed low student mathematical modeling skills, non-student-centered learning, and the unavailability of Student Worksheets appropriate to students' cognitive developmental stages. These conditions prompted the development of a Concrete Representational Abstract (CRA) approach-based student worksheet, relevant to Sustainable Development Goal (SDG) 4 Quality Education, to support quality education and student competency development. This study aims to develop a valid, practical, and effective CRA approach-based student worksheet to support junior high school students' mathematical modeling skills. This research is a research and development project using the Plomp model, which consists of three phases: preliminary research, prototyping, and evaluation. Product effectiveness was tested using a quasi-experimental design with a nonequivalent posttest-only control group design. Subjects were seventh-grade students of SMP Negeri 8 Tapung, Kampar Regency, Riau Province, with 25 students each in the experimental and control classes. Data were collected through questionnaires and tests, then analyzed using the Aiken index, percentages, and t-tests. The results showed that the CRA approach-based student worksheet was valid and effective in supporting students' mathematical modeling skills. The average posttest score for the mathematical modeling skills of students in the experimental class was 71.14, higher than that of the control class at 63.29. The t-test results showed a calculated t-value of 1.88 > the t-table of 1.68. Thus, the CRA approach-based student worksheet can be an innovative teaching material that supports quality mathematics learning and is relevant to achieving SDG 4.